2016
DOI: 10.13004/kjnt.2016.12.2.61
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Antiplatelet Therapy on Hemorrhagic Complications after Decompressive Craniectomy in Patients with Traumatic Brain Injury

Abstract: ObjectiveTraditionally, it is generally recommended that antiplatelet agent should be discontinued before surgery. However, decompressive craniectomy (DC) in patients with traumatic brain injury (TBI) is performed emergently in most cases. Therefore, DC cannot be delayed to the time when the effect of antiplatelet agent on bleeding tendency dissipates. In this study, we evaluated the effect of preinjury antiplatelet therapy on hemorrhagic complications after emergent DC in patients with TBI.MethodsWe retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…6 Furthermore, no difference in 7-day mortality rates with respect to AP intake was noted for patients undergoing decompressive hemicraniectomy. 11 This data is consistent with our results, which indicates that although patients suffering postoper-ative bleeding have higher mortality rates, postoperative bleeding does not appear to be directly affected by the preoperative intake of AP/AC medications.…”
Section: Mortality Rates In Tbi Patients Treated With Ap/acsupporting
confidence: 92%
See 2 more Smart Citations
“…6 Furthermore, no difference in 7-day mortality rates with respect to AP intake was noted for patients undergoing decompressive hemicraniectomy. 11 This data is consistent with our results, which indicates that although patients suffering postoper-ative bleeding have higher mortality rates, postoperative bleeding does not appear to be directly affected by the preoperative intake of AP/AC medications.…”
Section: Mortality Rates In Tbi Patients Treated With Ap/acsupporting
confidence: 92%
“…A study by Han et al showed a postoperative bleeding rate of 52.5% after decompressive craniectomy for TBI in patients treated with AP therapy. 11 The rate described is higher than in our cohort, however they only included patients undergoing hemicraniectomy with a midline shift > 5 mm. AP treatment was shown to be associated with higher mortality rates in TBI.…”
Section: Management Of Ap/ac Treatment In Neurosurgical Patientsmentioning
confidence: 59%
See 1 more Smart Citation
“…In patients with blunt head trauma, a previous meta-analysis of case-control and cohort studies showed only a slight and non-significant increased risk of death in patients who were taking pre-injury APA [ 790 ]. Further studies found both an association with worsening of the lesion [ 791 , 792 ], need for neurosurgical intervention [ 791 ], prolonged hospital stay and increased rate of disability [ 793 ], or no influence on survival [ 794 , 795 ], neurological outcome [ 786 , 796 ], need for neurosurgical intervention [ 794 , 797 ], haemorrhagic complications and need of re-operation after decompressive craniectomy [ 798 ], questioning the need for routine neurosurgical consultation [ 797 ] or repeat CT [ 799 ] in cases of mild head trauma or low-altitude falls in patients treated with APA (mainly aspirin, clopidogrel or both).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-eight were selected for full-text analysis of which 19 were excluded as they did not fulfill the inclusion criteria. Finally, 20 studies were included in this review (16)(17)(18)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Characteristics of included studies are presented in Table 1.…”
Section: Details Of Search and Included Studiesmentioning
confidence: 99%